Evaluation of the piezoelectric properties and voltage generation of flexible zinc oxide thin films. (6th May 2015) - Laurenti, M; Stassi, S; Lorenzoni, M; Fontana, M; Canavese, G; Cauda, V; Pirri, C F
Abstract: Local piezoresponse and piezoelectric output voltage were evaluated on ZnO thin films deposited by radio-frequency magnetron sputtering on hard Si/Ti/Au and flexible Cu-coated polyimide substrates. Three different thicknesses of ZnO films were studied (285 nm, 710 nm, and 1380 nm), focusing on characteristics like crystallinity, grain size, surface roughness, and morphology. Independent of the nature of the metal layer and the substrate, our results show that thicker films presented a higher level of crystallinity and a preferential orientation along the c -axis direction, as well as a lower density of grain boundaries and larger crystal sizes. The improvement of the crystalline structure of the material directly enhances its piezoelectric properties, as confirmed by the local characterizations performed by piezoresponse force microscopy and by the evaluation of the output voltage generation under the application of a periodical mechanical deformation on the whole film. In particular, the highest value of the d 33 coefficient obtained (8 pm V −1 ) and the highest generated output voltage (0.746 V) belong to the thickest films on hard and flexible substrates, respectively. These results envision the use of ZnO thin films—particularly on flexible substrates—as conformable, reliable, and efficient active materials for use in nanosensing, actuation, and piezoelectric nanogenerators.